Autoreduction of cyanoferrate(III) ions in a polymer electrolyte membrane: all solid state electrochemical and spectroscopic investigations - Parthasarathy, Meera; Gopinath, Chinnakonda S.; Pillai, Vijayamohanan K. (Chemistry of Materials, 2006)
The effect of dielectric confinement on proton-coupled electron-transfer behavior and spectroscopic properties of cyanoferrate ions in a polymer electrolyte membrane (Nafion) has been investigated in an ``all-solid-state'' electrochemical cell, using techniques such as cyclic voltammetry, zero current chronopotentiometry, electrochemical impedance, diffuse reflectance infrared Fourier transform spectroscopy (DRIFT), UV-visible spectroscopy, X-ray photoelectron spectroscopy (XPS), and electron spin resonance spectroscopy (ESR). From the above investigations, we found that cyanoferrate(III) ions undergo autoreduction in the ionomer matrix, for which a sulfonate-coupled mechanism has been proposed. This report demonstrates the effectiveness of the micellar interface in tuning the redox potential of the confined ions. A systematic analysis of the cyclic voltammetry and impedance data for the [Fe(CN)(6)](4)(-)- containing Nafion membrane enables the estimation of a standard rate constant for [Fe(CN) 6](4-) oxidation, k(o), as 5.44 x 10(-6) cm/s and a diffusion coefficient, D-o, as 1.3 x 10(-12) cm(2)/s. A similar calculation yields a value of 4.8 x 10(-12) cm(2)/s for the diffusion coefficient of protons and 9.1 x 10(-6) cm/s for the standard rate constant for hydrogen oxidation. The similarity in mass-transfer coefficients calculated for protons and [Fe(CN)(6)](4-) ions suggests a proton-coupled electron-transfer mechanism for the [Fe(CN)(6)](4-)/[Fe(CN)(6)](3-) couple. The results of the above investigations could have direct technological relevance for deciding catalyst materials having redox compatibility with the polymer electrolyte, especially in the preparation of catalyst-coated membranes (wherein the fuel-cell catalyst is directly coated onto the polymer membrane instead of on the carbon support).